Potential of South African medicinal plants as treatments for Alzheimer’s disease through Aβ42 protein reduction and identification of their active compounds - Maharaj, Vinesh J. (University of Pretoria, 2020)
Thesis (PhD (Chemistry))--University of Pretoria, 2020.